(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article analyzes the existing problems in the process of increasing the tax potential of the regions of the Republic of Uzbekistan and develops practical solutions for their elimination. The regional tax potential is seen as one of the important factors in strengthening the income base of local budgets, ensuring fiscal independence and promoting macroeconomic stability. The article reveals the main problems such as insufficient formation of the tax base, wide coverage of the informal economy, systemic shortcomings in the tax administration, underdevelopment of economic infrastructure and low level of investment attractiveness. The article also developed proposals for identifying territorial tax opportunities on the basis of advanced foreign experiments, their full mobilization and optimizing fiscal policy in the cross-sectional areas. The author reasoned that it is possible to develop tax potential by digitizing the tax database, supporting small business and private entrepreneurship in the regions, increasing the tax culture and improving inter-budgetary relations. The results of the article can serve to improve state tax policy at the local level, ensure economic equality between regions and strengthen socio-economic stability.